Measles Vaccine Effectiveness at Borthong District of Chonburi - Raxkshib, Pramote; Cham-on, Sommai; Reaunkong, Junpen; Pongpisitson, Prasert; Tummakitikun, Neunnoi; Sombat, Soopattra (Journal of Health Science of Thailand, 1995)
The measles vaccine effectiveness in children age 1-12 years at Borthong district of Chonburi province were surveyed and evaluated during January 1994 to February 1994. The total number of 338 children were included and divided into 3 groups; for 1-4 years, 5-9 years and for 10-14 years. The results of the measles vaccine effectiveness for 1-4 years and 5-9 years are 58.96% and 70.28% respectively.